Implementing integrated care in ophthalmology: a community case study - Nikita, Eleni; Allen, Richard; Khambati, Hussein; Tsounis, Christos; Tucker, William; Malcolmson, Kirsten; Hingorani, Melanie; Marjoram, Zoe (Frontiers in Medicine, 2023)
Introduction: In 2017, in a context of financial and patient care challenges, Moorfields Eye Hospital in the borough of Croydon launched the first Ophthalmology Integrated Care Contract in the United Kingdom.Description: A realistic, systematic approach is presented for an efficient implementation of an integrated care ophthalmology contract under a lead provider. The main elements of the new contract are portrayed.Discussion: A new healthcare contract that would lead to system-wide transformation requires significant time commitment, vision, shared narrative, leadership, multi-functional working culture, shared accountability of all participating parties and education and support of all parties involved. Key levers to elevate the quality of care are collaborative relationships between health professionals, investing in information and technology and facilitating bottomup innovation.System-wide changes such, as integrated care contracts are possible, although the interplay between context, design and implementation is more complex than expected.